Impaired deformability of erythrocytes and neutrophils in children with newly diagnosed insulin-dependent diabetes mellitus - Linderkamp, Otwin; Ruef, Peter; Zilow, Eugen; Hoffmann, Georg F. (Diabetologia, 1999)
Aims/hypothesis. Abnormal rheological properties of erythrocytes, leucocytes and plasma may have a role in the development of diabetic microangiopathy. We hypothesized that changed haemorrheological variables may already be found in children with onset diabetes. Methods. Erythrocyte deformation (rheoscope), neutrophil deformation (micropipette), erythrocyte aggregation, blood and plasma viscosity were measured in 15 children with insulin-dependent diabetes mellitus before initiation of insulin treatment and 4 to 6 weeks later, 15 diabetic children treated with insulin for 5 to 8 years, 15 healthy children and 15 healthy adults. Results. At a low shear stress of 0.6 Pa, erythrocyte deformation was decreased in the diabetic children before (-28 %), after 4 to 6 weeks (-22 %) and after 5 to 8 years (-17 %) of insulin treatment compared with healthy children. More active neutrophils were counted in the untreated diabetic children (9 ± 6 %) than in healthy children (3 ± 2 %). Deformability of passive neutrophils was greatly decreased in the children with onset diabetes and moderately reduced in the diabetic children who were treated with insulin. Neutrophil deformation (r = -0.52) and erythrocyte deformation at 0.6 Pa (r = -0.62) were inversely related to haemoglobin A1 c. Haematocrit and blood viscosity were increased in the untreated children and in the children treated with insulin for 5 to 8 years. Plasma viscosity and erythrocyte aggregation were similar in the three groups of children. Conclusion/interpretation. Decreased erythrocyte deformation at low shear force, increased count of active neutrophils and impaired deformability of passive neutrophils may increase the risk for acute cerebro-vascular complications in children with uncontrolled insulin-dependent diabetes mellitus. [Diabetologia (1999) 42: 865-869]